KONSEP DIRI MAHASISWA UNIVERSITAS PASUNDAN DALAM KONTEKS KOMUNIKASI ANTARBUDAYA - Rahmi Aini; Teuku Yuliansyah; Aura Angelisa; Feni Oktami Putri (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
University development and competition, both public and private, to be the best is now required. Each of these institutions, whether a university, institute, or high school, is required to be able to win interest and trust from the public, so it must pay attention and maintain good quality for its users. Organizational culture has an important role in an organization. Pasundan University implements three pillars in its organizational culture, namely